A mineralogical and geochemical application for determining hydrothermal alteration zones associated with volcanic-hosted massive sulphide deposits at Tasik Chini area, Peninsular Malaysia. (October 2022) - Basori, Mohd Basril Iswadi; Zaw, Khin; McNeill, Andrew; Large, Ross Raymond
Abstract: The volcanic-hosted massive sulphide (VHMS) deposits of the Tasik Chini area, Peninsular Malaysia are hosted by Permian felsic volcanic rocks (∼ 290 Ma) of rhyolitic to rhyodacitic composition and comprise two deposits (Bukit Botol and Bukit Ketaya). Although the ores and the felsic volcanic host rocks of these deposits have metamorphosed to greenschist facies and were affected by a complex deformation history, the hydrothermal alteration zones associated with mineralization are preserved and show systematic mineralogical and geochemical changes with increasing proximity to the ore bodies. The geometry of alteration assemblages of the Bukit Botol and Bukit Ketaya deposits shows they occur as semi-conformable or stratabound zones around the ore lenses. According to petrography study and short wavelength infrared (SWIR) spectra measurements supported by X-Ray diffractometer (XRD), the Bukit Botol deposit is characterised by proximal quartz-sericite-pyrite and distal quartz-sericite alteration zones, whereas distal quartz-chlorite-sericite-pyrite-pyrophyllite ± kaolinite and proximal quartz-chlorite-pyrite ± carbonate ± pyrophyllite form the alteration assemblages of the Bukit Ketaya deposit. The geochemical data is coherent with the mineralogical characteristics, using the Ishikawa alteration (AI) and chlorite-carbonate-pyrite (CCPI) indexes, showing the important of chlorite and sericite formation in the ore proximal and ore distal zones. In addition, the molar elemental ratios of Na2 O/Al2 O3 versus K2 O/Al2 O3 and MgO/Al2 O3 versus K2 O/Al2 O3 support that the abundance of muscovite (sericite) and chlorite controlled the intensity of alteration at the both deposits. The results of this study indicate that the combination of mineralogy and geochemistry studies help in defining specific alteration styles and related mineral geochemical variations of the VHMS deposits in Tasik Chini area. Highlights: Hydrothermal alteration zones from VHMS deposits in Tasik Chini area were characterised using mineralogical and lithogeochemical studies. The hydrothermal alteration zones are controlled by hydrothermal ﬂuids pathway on their formation. The conditions of fluid-rock interaction controlled the different alteration minerals and its chemical attributes.